(untitled) (Educological discourse, 2014)
The article deals with the resolutions adopted at the first congress of higher educational institutions of Ukraine (April 1918, Kyiv). Attention was drawn to the decision of the congress on expanding of the autonomy’s universities and the need to build the «Councils of higher educational institutions». Raised the issue of the Ukrainian citizenship and Ukrainization of higher educational institutions. Identified a number of conceptual provisions concerning the restructuring’s system of higher education on a new basis, which was essential for the further development of education in Ukraine. Lit the problem of financing universities in the early twentieth century. Filed payroll of temporary bureau, selected to prepare for the next congress.